Minimal Synthetic Cells to Study Integrin‐Mediated Adhesion. Issue 42 (7th August 2015) - Frohnmayer, Johannes P.; Brüggemann, Dorothea; Eberhard, Christian; Neubauer, Stefanie; Mollenhauer, Christine; Boehm, Heike; Kessler, Horst; Geiger, Benjamin; Spatz, Joachim P.
Abstract To shed light on cell‐adhesion‐related molecular pathways, synthetic cells offer the unique advantage of a well‐controlled model system with reduced molecular complexity. Herein, we show that liposomes with the reconstituted platelet integrin αIIbβ3 as the adhesion‐mediating transmembrane protein are a functional minimal cell model for studying cellular adhesion mechanisms in a defined environment. The interaction of these synthetic cells with various extracellular matrix proteins was analyzed using a quartz crystal microbalance with dissipation monitoring. The data indicated that integrin was functionally incorporated into the lipid vesicles, thus enabling integrin‐specific adhesion of the engineered liposomes to fibrinogen‐ and fibronectin‐functionalized surfaces. Then, we were able to initiate the detachment of integrin liposomes from these surfaces in the presence of the peptide GRGDSP, a process that is even faster with our newly synthesized peptide mimetic SN529, which specifically inhibits the integrin αIIbβ3.